Bodies of Evidence. Ancient Anatomical Votives Past, Present and Future - Jane Draycott; Emma-Jayne Graham (Les Carnets de l’ACoSt)
The papers presented in this volume are the result of the conference Bodies of Evidence: Re-defining Approaches to the Anatomical Votives that was held at the British School in Rome in 2012. Additional papers area also included